Quantum leadership : new consciousness in business - Tsao, Frederick; Laszlo, Christopher (Tantor Media, Inc., 2019)
In this new book, Frederick Chavalit Tsao and Chris Laszlo argue that current approaches to leadership fail to produce positive outcomes for either businesses or the communities they serve. Employee disengagement and customer fickleness remain high, resulting in a lack of creativity and collaboration at all levels of entrepreneurial activity. Investor demand for Environmental, Social, and Governance (ESG) continues to be poorly integrated into profit strategies. Drawing on extensive research, this book shows how changing a person's consciousness is the most powerful lever for unlocking his or her leadership potential to create wealth and serve humankind. A wide range of practices of connectedness provide the keys. The journey to higher consciousness changes people at a deep intuitive level, combining embodied experience with analytic-cognitive skill development. Tsao and Laszlo show how leaders who pursue this journey are more likely to flourish with significant benefits to both business and society. These include greater creativity and collaboration along with an increased capability to inspire people and produce lasting change. Listeners will come away with a deep understanding of quantum leadership and the day-to-day practices that can help them achieve greater effectiveness and well-being at work.